Biomolecule arrays using functional combinatorial particle patterning on microchips - Löffler, Felix; Schirwitz, Christopher; Wagner, Jennifer; König, Kai; Torralba, Gloria Collados; Hausmann, Michael; Bischoff, F. Ralf (Advanced functional materials, 2012)
Biofunctionalization of surfaces in a microarray format has revolutionized biological assay applications. Here, a microarray system based on a microelectronic chip is presented that allows for a versatile combinatorial in situ molecule synthesis with very high density. Successfully demonstrating an application for peptide array synthesis, the method offers a compact approach, high combinatorial freedom, and, due to the intrinsic alignment, high and reproducible precision. Patterning the chip surface with different microparticle types which imbed different monomers, several thousand different molecule types can be simultaneously elongated layer‐by‐layer by coupling the particle imbedded monomers to the molecules growing on the chip surface. This technique has the potential for a wide application in combinatorial chemistry, as long as the desired monomeric building blocks are compatible with the chemical process.
Gesehen am 26.10.2018